Literature Review: Hubungan Mencuci Tangan dan Konsumsi Makanan Dengan Kasus Diare Pada Anak Sekolah di Indonesia - Pradita Setiawan,; Lilis Sulistyorini, (Student Scientific Creativity Journal, 2023)
One of the main causes of mortality in children, as well as an important factor leading to malnutrition is Diarrhea. The prevalence of diarrhea among the 5-14 age group ranks highest after the toddler and elderly age groups. In 2018, the number of diarrhea cases among all age groups served by healthcare facilities increased by 229,734 cases from the previous year of 2017. Children who have persistent diarrhea may experience subpar results in terms of their growth and development.. The purpose of this study is to ascertain the connection between handwashing practices and dietary habits and the prevalence of diarrhea in school-aged children.. The research method used is a Literature Review, by searching for research articles sourced from the electronic database Google Scholar using keywords such as diarrhea, handwashing habits, food consumption, and students. From the analysis of 5 articles, it was found that the habit of washing hands with soap and maintaining nail hygiene can prevent the occurrence of diarrhea in children. A good food consumption pattern also has a lower risk of experiencing diarrhea. Age differences in children are also related to the incidence of diarrhea, where younger children are more susceptible to experiencing diarrhea.